Cybersecurity Vulnerability Analysis of Russian Strategic Nuclear Missile Systems: Implications for Ukraine and NATO - Meseguer González, Juan de Dios (Journal of the Spanish Institute for Strategic Studies, 2026)
This article analyzes the cyber vulnerability of the Russian Federation’s strategic nuclear missile systems, focusing on implications for regional security in Ukraine and NATO’s strategic deterrence. Using a mixed-method approach—combining open-source intelligence, attack vector simulation, and doctrinal review—the study identifies critical weaknesses in command-and-control systems, communication links, and authentication protocols. Findings indicate that legacy Soviet-era components pose significant risks of cyber intrusion, potentially undermining strategic stability. The article concludes that strengthening cyber defense capabilities and NATO–Ukraine coordination in cyber intelligence is essential to counter potential unconventional escalation scenarios. Key words: cyber vulnerability, strategic missiles, nuclear deterrence, Ukraine, NATO, hybrid security.